PENGARUH PEMBELAJARAN SUGESTI IMAJINASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA - Muh. Ihsan; Farida Fitriani (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2019)
Imagination Suggestion Model is not yet popular among teachers, teachers still use a learning model that is still monotonous, so that the learning process is often found that students are not actively participating in the learning process. The purpose of this study was to determine the effect of the Imagination Suggestion Model on Student Learning Outcomes in Indonesian Language Subjects Class VIII at SMPN 3 Gunungsari, West Lombok Regency in 2018/2019 Academic Year. Data collection methods use tests, documentation and interviews as a complement. As for data analysis using the t test formula. After the research is carried out, the data is entered into the work tebel, then performed calculations using the formula. T-test results show the value of t calculated is greater than the value of t table at a significance level of 5% with db = 20-1 = 19 (3.703> 2.093) then the null hypothesis (H0) is rejected while the alternative hypothesis (Ha) is accepted. The Conclusion There Is The Effect Of Imagination Suggestion Model On Student Learning Outcomes In Indonesian Language Subjects Class VIII at SMPN 3 Gunungsari, West Lombok Regency, 2018/2019 Academic Year. In other words, this research is significant.